The Updating in Satir’s Family Therapy Model - Yıldırım, Neşide (European Journal of Multidisciplinary Studies, 2021)
Virginia Satir (1916-1988) is one of the first experts who has worked in the field of family therapy in the United States. In 1951, she was one of the first therapists who has worked all members of the family as a whole in the same session. She has concentrated her studies on issues such as to increase individual's self-esteem and to understand and change other people's perspectives. She has tried to make problematic people compatible in the family and in the society through change. From this perspective, change and adaptation are the two important concepts of her model. This is a state of being and a way to communicate with ourselves and others. High self-confidence and harmony are the first primary indicator of being a more functional human. She starts her studies with identifying the family. She uses two ways to do this; the first one is the chronology of the family that is history of the family, the second one is the communication patterns within the family. With this, she updates the status of the family. Updating is the detection of the current situation. The detection of the situation, in other words updating, constitutes the very essence of the model that she implements. In this study, communication patterns within the family are discussed for the updating, the chronological structure has not been studied. The characteristics of family communication patterns, the model of therapy that is applied by Satir for these patterns and the method which is followed in the model are discussed. According to her detection, the people who face with problems, use one of those four patterns or a combination of them. These communication patterns are Blamer, Sedative/Accepting, distracter/irrelevant and rational. Satir expresses that these four patterns are not solid and unchanging but all of them “can be converted”. For example, if one of the family members is usually using the soothing (sedative/accepting) pattern, in this case, it means that he/she wants to give the message that he/she is not very important in the inner world of the individual itself. However, if such a communication pattern is to be used repeatedly by an individual, he/she must know how to use it. According to Satir, this consciousness may be converted to a conscious gentleness and sensitivity that is automatically followed to please everyone. This study was carried out by using the copy of Satir’s book, which was originally called “The Conjoint Family Therapy” and translated into Turkish by Selim Ali Yeniçeri as “Basic Family Therapy” and published in Istanbul by Beyaz Yay?nlar? in 2016. It is expected that the study will provide support to the education of the students and family therapists.
Keywords: Virginia Satir, Family, Therapy, Model, Update.